Albumin-to-Alkaline Phosphatase Ratio: A Novel Prognostic Index for Hepatocellular Carcinoma. (9th February 2015) - Chan, Anthony W. H.; Chan, Stephen L.; Mo, Frankie K. F.; Wong, Grace L. H.; Wong, Vincent W. S.; Cheung, Yue-Sun; Chan, Henry L. Y.; Yeo, Winnie; Lai, Paul B. S.; To, Ka-Fai
Abstract : Prognosis of patients with hepatocellular carcinoma (HCC) depends on both tumour extent and hepatic function reserve. Liver function test (LFT) is a basic routine blood test to evaluate hepatic function. We first analysed LFT components and their associated scores in a training cohort of 217 patients who underwent curative surgery to identify LFT parameters with high performance (discriminatory capacity, homogeneity, and monotonicity of gradient). We derived a novel index, albumin-to-alkaline phosphatase ratio (AAPR), which had the highest c-index (0.646) andχ 2 (24.774) among other liver biochemical parameters. The AAPR was an independent prognostic factor for overall and disease-free survival. The adjusted hazard ratio of death and tumour relapse was 2.36 (P = 0.002 ) and 1.85 (P = 0.010 ), respectively. The independent prognostic significance of AAPR on top of 5 commonly used and well established staging systems was further confirmed in 2 independent cohorts of patients receiving surgical resection (n = 256 ) and palliative therapy (n = 425 ). In summary, the AAPR is a novel index readily derived from a simple low-cost routine blood test and is an independent prognostic indicator for patients with HCC regardless of treatment options.